2015
DOI: 10.5194/tc-9-13-2015
|View full text |Cite
|
Sign up to set email alerts
|

Independent evaluation of the SNODAS snow depth product using regional-scale lidar-derived measurements

Abstract: Abstract. Repeated light detection and ranging (lidar) surveys are quickly becoming the de facto method for measuring spatial variability of montane snowpacks at high resolution. This study examines the potential of a 750 km 2 lidar-derived data set of snow depths, collected during the 2007 northern Colorado Cold Lands Processes Experiment (CLPX-2), as a validation source for an operational hydrologic snow model. The SNOw Data Assimilation System (SNODAS) model framework, operated by the US National Weather Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…5). This follows previous reports that without sufficient data, estimates of snow depth under these conditions can be difficult and error prone due to the underlying variance in elevation within grid boundaries [Hedrick et al, 2015]. Clow et al [2012] showed that for over-forested regions of the Colorado Rockies, SNODAS estimates of snow depth accounted for as much as 72% of the variance line (1-km resolution) in forested areas, but SNODAS was only able to account for 16% of snow-depth variance in areas above the treeline.…”
Section: Snow Depthsupporting
confidence: 85%
“…5). This follows previous reports that without sufficient data, estimates of snow depth under these conditions can be difficult and error prone due to the underlying variance in elevation within grid boundaries [Hedrick et al, 2015]. Clow et al [2012] showed that for over-forested regions of the Colorado Rockies, SNODAS estimates of snow depth accounted for as much as 72% of the variance line (1-km resolution) in forested areas, but SNODAS was only able to account for 16% of snow-depth variance in areas above the treeline.…”
Section: Snow Depthsupporting
confidence: 85%
“…Although SNODAS assimilates MODIS imagery into the model, it does not appear to capture the finer elevation patterns we found using the MOD10A product (Fig. 7), which is consistent with challenges reported by other SNODAS verification efforts in complex terrain (Clow et al, 2012;Hedrick et al, 2015). The Great Basin shows tremendous sensitivity to snow ephemerality from topography and elevation 15 and thus, represents an area where improvements in the physically-based modeling of shallow snow and rain-snow transition elevations will be critical to predicting snow water resources under a variable and changing climate.…”
supporting
confidence: 78%
“…11). Blowing snow sublimation was not the dominant cause of snow ephemerality in the Great Basin for any year, but its known that SNODAS struggles to represent wind redistribution of snow Clow et al (2012);Hedrick et al (2015). The mechanisms causing snow ephemerality that can be inferred from the SNODAS model have important implications for water availability in the Great Basin, but we lack confidence in the model fidelity in these shallow snowpacks.…”
mentioning
confidence: 97%
“…Existing techniques include terrestrial or airborne laser scanning (e.g., Hopkinson et al, 2004;Deems et al, 2006Deems et al, , 2013Prokop et al, 2008;Dadic et al, 2010;Grünewald et al, 2010Grünewald et al, , 2013Lehning et al, 2011;Hopkinson et al, 2012;Grünewald and Lehning, 2015;Hedrick et al, 2015), SAR (synthetic aperture radar, Luzi et al, 2009), aerial photography (Blöschl and Kirnbauer, 1992;König and Sturm, 1998;Worby et al, 2008), time-lapse photography (Farinotti et al, 2010), and optical and micro-wave data from satellite platforms (Parajka and Blöschl, 2006;Dietz et al, 2012). The good performance of these methods has been widely discussed, but survey expenses are still a constraint (Hood and Hayashi, 2010).…”
Section: Introductionmentioning
confidence: 99%